2014
DOI: 10.1111/1574-6968.12512
|View full text |Cite
|
Sign up to set email alerts
|

Development of multiplex loop-mediated isothermal amplification assays to detect medically important yeasts in dairy products

Abstract: Rapid detection of yeast contamination is important in the food industry. We have developed loop-mediated isothermal amplification (LAMP) assays to detect the emerging opportunistic pathogenic yeasts: Candida albicans, Candida glabrata, Candida tropicalis, the Candida parapsilosis group, Trichosporon asahii, and Trichosporon mucoides. These yeasts may cause deep-seated candidiasis or trichosporonosis. Four LAMP primer sets specific for Candida were designed to target the internal transcribed spacer 2 (ITS2) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…Although there is no theoretical limit to the number of primers to be used in a multiplex LAMP reaction, spurious-prone amplification among primers limits the establishment of specific reactions. A multiplex LAMP assay combining 21 primers targeting four Candida species has been reported21. The high specificity of primers used in this study has been reported and validated previously1012, and there was no spurious amplification products in our multiplex LAMP reaction, which showed 100% inclusivity and 100% exclusivity for the detection of 19 bacterial strains including Salmonella spp.…”
Section: Discussionsupporting
confidence: 76%
“…Although there is no theoretical limit to the number of primers to be used in a multiplex LAMP reaction, spurious-prone amplification among primers limits the establishment of specific reactions. A multiplex LAMP assay combining 21 primers targeting four Candida species has been reported21. The high specificity of primers used in this study has been reported and validated previously1012, and there was no spurious amplification products in our multiplex LAMP reaction, which showed 100% inclusivity and 100% exclusivity for the detection of 19 bacterial strains including Salmonella spp.…”
Section: Discussionsupporting
confidence: 76%
“…This approach however is difficult for non-culturable organisms and dependent on unique pathogen surface antigens. Turbidity monitoring [ 39 ] to achieve multiplex LAMP has also been reported; however, this approach has poor reproducibility and requires extensive design optimization to achieve differentiable time-to-positivity values.…”
Section: Discussionmentioning
confidence: 99%
“…36 LAMP with a detection limit of 1ng has also been successfully used for rapid detection of Porphyromonas gingivalis and Aggregatibacter actinomycetemcomitans, both of which cause periodontitis in humans. 37 LAMP assays for detecting yeasts, 38 influenza viruses 39 and Plasmodium have been developed. 40 Different companies have also designed commercial LAMP kits (Table 2) for the detection of Salmonella, [41][42][43] verotoxin-producing Escherichia coli [44][45][46] and Campylobacter.…”
Section: Loop-mediated Isothermal Amplification (Lamp)mentioning
confidence: 99%